ENT 530 Social Media Portfolio: Lab Box / Siti Zaiyanna Atasha Dzinal Abidin - Dzinal Abidin, Siti Zaiyanna Atasha (2021)
The Lab Box was well-known on October 2020 and our product trademark is "Your happiness is our priority" which means we are expert planner give our customer the best service. Besides, “The Lab Box" does indicate to the name of the surprise box which is inspired by the purpose for doing a laboratory experiment under highly controlled. We’re choosing The Lab Box as our new product. That makes the product look different from others because customers cannot choose the color because it’s a surprise and it’s no fun to know what’s inside. We will experiment which is decide the best combo for customer’s box. The Lab Box is also known as surprise box. But I make two box full of convenient stuff inside in order to make it more amazing. The combination of this two will make everyone obsess especially our target audience. For example, young people age 18-24 female. Our objective is to ensure customers are satisfied with our surprise box. Some people are too busy to prepare it for themselves or for their loved ones because it take times and efforts. People nowadays prefer instant compare to home-made. As a result, The Lab Box is ready to serve our customers. Since our first day of launch, our product was sold more than 20 boxes every week. We are looking forward for another methods to growing our business not only by using a Facebook page to reach more customers.